Use of factorial design of experiments in the development of the zirconia toughened hydroxyatite composites - Genç, Yasin (My University, 2003)
Hydroxyapatite (HA) bioceramic is currently being used in orthopedics and density, for reconstruction or repair of diseased or injured bone, but with limited success due to its poor mechanical properties compared with human bone. This work focuses on improving the mechanical properties of HA through the addition of zirconia doped with 3mol% yttria. In this study, two different composites are studied: enamel derived HA- ZrO2 composites and synthetic HA- ZrO2 composites. The enamel HA powder used in this study was derived from freshly extracted human teeth. After calcination at 850 C, only the enamel part of the teeth was used. The experiments are designed using general 'A x B' full factorial design. The factors studied are the reinforcement content of ZrO2 addition and the sintering temperature. For enamel derived HA- ZrO2 composites ZrO2 was added by 5wt% and 10wt%, for synthetic HA-ZrO2 by 0wt%, 5wt%, and 10wt%. Compacts of different compositions were sintered at 1000 C, 1100 C, 1200 C, and 1300 C for 4 hours. The density, microhardness and compression tests were performed. The influence of both factors on density, microhardness, and compression strength were statistically examined. The average density, Vickers hardness, and compression strength for enamel derived HA-Zr and synthetic HA-Zr compacts containing 10wt% Zr and sintered at 1300 C were found as 3,001 0.017 g/ cm3 and 2,981 0.065 g/ cm3, 316 54 HV (kg/ mm2) and 329 89 HV (kg/ mm2), 97.02 18 MPa and 30.10 15 MPa, respectively. The X-Ray diffraction analysis was performed and related with the mechanical properties of the composites, consequently. Hidroksiapatit (HA) biyoseramiği ortopedi ve dişhekimliğinde hastalıklı ya da yaralanmış kemiğin yeniden yapılandırılmasında ya da tamirinde halen kullanılmaktadır. Ancak insan kemiği ile karşılaştırıldığında hidroksiapatitin zayıf mekanik özellikler göstermesi başarısını sınırlamaktadır. Bu çalışma HA'nın mekanik özelliklerinin 3mol% yitria ile stabilize edilmiş zirkonya ilavesi ile geliştirilmesine odaklanmıştır. Bu çalışmada iki değişik kompozit malzeme üzerinde çalışılmıştır: mineden türetilmiş hidroksiapatit-zirkonya kompozitleri ve sentetik hidroksiapatit-zirkonya kompozitleri. Bu çalışmada kullanılan mine hidroksiapatiti çekilmiş insan dişinden türetilmiştir. Dişler 850 C de kalsine edilmiş ve dişlerin sadece mine kısmı kullanılmıştır. Deneyler, genel 'AxB' tam faktörel dizayn tekniği kullanılarak planlanmıştır. Üzerinde çalışılan faktörler güçlendirici olarak eklenen zirkonya miktarı ve sinterleme sıcaklığıdır. Mine HA-ZrO2 kompozitler için %5 ve %10 oranlarında, sentetik HA- ZrO2 kompozitler için %0,%5 ve %10 oranlarında zirkonya eklenmiştir. Değişik kompozisyonlardaki örnekler 1000 C,1100 C,1200 C ve 1300 C de 4 saat süreyle sinterlenmiştir. Numunlerin yoğunlukları ölçülmüş, mikrosertlik ve basma testleri yapılmıştır. Her iki faktörün yoğunluk, mikrosertlik ve basma mukavemeti üzerindeki ektileri istatistiksel olarak incelenmiştir. %10 zirkonya içeren ve 1300 C de sinterlenen diş minesinden elde edilen HA- ZrO2 ve sentetik HA- ZrO2 numunelerinin yoğunluk, Vickers sertliği ve basma mukavemeti değerleri sırasıyla 3,001 0.017 g/ cm3 ve 2,981 0.065 g/ cm3, 316 54 HV (kg/ mm2) ve 329 89 HV (kg/ mm2), 97.02 18 MPa ve 30.10 15 MPa olarak bulunmuştur. X-Işınları difraksiyon analizleri yapılmış ve sonrasında mekanik özelliklerle ilişkilendirilmiştir.
Keywords: Hastalıklar; İskelet kas sistemi hastalıkları; Kemik hastalıkları; Tasarım; Teknoloji (Uygulamalı bilimler); Tıp bilimleri